Analysis of the Procurement Process of Medicine in Pharmacy Installations Lubuk Basung Regional General Hospital - Septhia Putri Andini; Dian Novita; Tri Wijayanto (Miracle Journal Get Press, 2024)
Procurement is an activity carried out exist to provide goods that initially did no exist. The problem with drug procurement that researchers found at the Lubuk Basung Regional Hospital Pharmacy Installation was that there were vacancies in several drug items at distributors so that the drugs that were supposed to be given to patients ran out of stock. The study took place between June and July 2023. In-depth interviews and a document examination were used to acquire data. The results of this research are that the Lubuk Basung Regional Hospital Pharmacy Installation already has an SPO, but the latest SPO has not been issued, planning is carried out to avoid vacancies and excess drug stock which result in expired dates in the Pharmacy Installation. The drug procurement process uses two methods, namely the direct procurement method (e-purchasing & PBF) and the donation method (grants). accordance based on the findings of this inquiry, it can be inferred that the drug planning process there is an SPO and the activities carried out are in accordance with SPO issued. The drug procurement process has been carried out well using two methods, procurement is carried out every 3 months and once a month according to the drug consumption pattern of the previous period. It is recommended to the Hospital the latest SPO be issued immediately, to carry out regular evaluations on every order of goods so that there are no errors or mistakes in receiving the goods.